Understanding the Well-Being of General Surgery Residents. Issue 3 (March 2021) - Felton, Jessica; Martin, Olivia; Kubicki, Natalia; Kidd-Romero, Sarah; Kavic, Stephen M.
Background: In 2017, the Accreditation Council for Graduate Medical Education program guidelines changed to include a section that requires programs to optimize resident and faculty member well-being. There is still a poor understanding of general surgery resident wellness, and there are few well-established wellness programs. Methods: We created a novel 50-question anonymous survey to assess burnout, depression, and wellness that was distributed to the general surgery residents as part of a pilot study. Univariate analysis was performed to assess wellness and wellness changes. Bivariate analysis was performed to determine the association between wellness variables and gender, age, and postgraduate year (PGY) level. Results: Thirty-five of 55 residents participated in the survey. Over half of the residents (54%) reported gaining weight during residency. Nearly 70% reported working while having an ongoing family issue, and 77% worked at least once while ill. Fourteen residents (40%) reported that their wellness worsened over the previous academic year, while 7 (20%) reported that it remained the same, and 11 (31%) reported that it improved. These changes varied significantly by the PGY level ( P < .01). Age (younger vs older than 30) and sex were found to be effective measure modifiers of the association between wellness change and PGY level. Discussion: The overall wellness of the general surgery residents at our institution varies greatly. Poor wellness may lead to inferior patient care, burnout and depression, and negative resident morale. Residency programs need to implement programming to address wellness deficiencies.